Exchange Rate Volatility and Central Bank Actions in Egypt: Generalized Autoregressive Conditional Heteroscedasticity Analysis - Elsherif, Marwa A. (International Journal of Economics and Financial Issues, 2016)
Egypt has passed through different development stages, followed different exchange rate regime at each, ranging from fixed to floating. This study tries to examine empirically how Central Bank of Egypt actions influence exchange rate volatility using GARCH (1. 1) model under Gaussian normal distribution, considering monthly observations of Egyptian Pound against US Dollar, spanning the period from 2003 after the adoption of floating exchange rate regime till 2014. The model includes three exogenous variables as they can contribute to the exchange rate volatility; interest rate differentials, trade balance and official reserves. Results show the presence of volatility clustering but this volatility shocks are not so quite persistent. Central Bank actions impacted exchange rate volatility positively through interest rate, and negatively through reserves amount. Finding solutions to trade deficits to encourage exports and tackle down imports can hinder exchange rate volatility in Egypt. Keywords: Exchange Rate Volatility, GARCH, Monetary Policy JEL Classifications: C23, E58